Laser spectroscopy for sensing : fundamentals, techniques and applications - Baudelet, Matthieu (Woodhead Publishing, 2014)
Annotation Laser spectroscopy has become a diverse field, with applications in numerous areas of physics, chemistry, and biology. Developments in ultrafast laser technology have led to improvements in laser spectroscopy techniques. Laser spectroscopy can be used to sense solids, liquids, and gases for medical diagnostics, environmental monitoring, and forensic investigations, and it is critical to the understanding of many industrial and biological processes. This book, with contributions from academics and industry practitioners, covers fundamentals of laser spectroscopy, describes the techniques of laser spectroscopy, and discusses the applications of laser spectroscopy, such as the detection of chemical, biological and explosive threats.
Keywords: Laser spectroscopy.; elektronické knihy; electronic books